Jah, Omar. “Globalization and Social Changes: Culture in the Muslim World,” Year 10, Issues 37-38 (Summer-Fall 1425 AH/ 2004 CE), Pp. 203-227. - جاه, عمر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2004)
Omar Jah’s article aims to shed light on the possible effects of globalization on the social and cultural fabric of Muslim societies. It also seeks to emphasize the necessity of protecting the basic principles of Islam from the forces of globalization. It highlights aspects of this new phase of imperialism that has been, and still is, controlling the history of the modern world; holding that imperialism and globalization as two sides of the same coin. The central points of his article address: globalization in its political, cultural, and economic frameworks; the Islamic worldview; the theory of culture in Islam; the importance of knowledge; dangers of globalization; the effects of globalization on the Muslim world; and international globalization. It concludes by offering recommendations pertaining to these points.